Nghiên cứu đặc điểm động học quá trình phân hủy axit 2,4-diclophenoxy axetic trong môi trường nước bằng hệ xúc tác Fe(III)-TAML/H2O2 - Hữu, Đào Thế; Tấn, Đinh Ngọc; Phong, Nguyễn Hùng (Vietnam Journal of Chemistry, 2016)
Iron(III)–TAML (Tetra-Amindo Macrocyclic Ligand) complex is an advanced green oxidation catalyst and reactive capabilities of the catalytic through the catalyzed activation process by peroxide to form Fe-oxo intermediates that the oxidation number of Fe element is +4 or +5. Although many factors influence the of the decomposition kinetic of 2,4-D in water by Fe(III)-TAML/H2O2 catalytic system but two factors are pH and the concentration ratio of Fe (III) -TAML/2.4-D are more important than the whole. Degradation kinetics of 2,4-D in water by Fe(III)-TAML/H2O2 catalytic system are researched by changing of 2,4-D concentration, that changings are determined by using high-performance liquid chromatography analysis method (HPLC), the peaks of 2,4-D characterized by the retention time t = 4.17 min. With pH values ranging from 7 to 12, kinetic of oxidation reaction fit to the pseudo first-order form. While changing the mole concentration ratio of Fe(III)-TAML/2,4-D, if the ratio is low showing that the reaction rate is first-order but when the mole concentration ratio of Fe(III)-TAML/2,4-D is high, the pseudo first-order form is not true. When change the temperature of the reaction we can calculate the k’ rate constants and activation energy of the oxidation reaction Ea = 17.027 (kJ /mol). Keywords. Kinetic, Fe(III)–TAML/H2O2 catalyst, degradation of 2,4-D.